Organizational and Economic Foundations of Logistic Management of Foreign Economic Activity of Industrial Enterprises - Shuliar, N. M. (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2025)
Organizational and Economic Foundations of Logistic Management of Foreign Economic Activity (FEA) of Industrial Enterprises involve the organization and optimization of all flow processes related to export/import operations, as well as the management of costs, risks, and compliance with state regulations. This includes the construction of logistics systems that ensure the delivery of goods of the required quality, quantity, and at the right time and place, considering economic efficiency and legislative requirements. This article explores the theoretical and practical aspects of forming an effective organizational and economic mechanism for logistic management of foreign economic activity in Ukrainian industrial enterprises. The study analyzes modern management principles of FEA under globalization and increasing competition, particularly the focus on financial success, consumer interest prioritization, scientifically grounded decisions, innovation, and adaptability. Special attention is given to the key areas of FEA (export-import operations, supply chain management, investment activity, engineering services) and the role of logistics as an integrative component in supporting these processes. The article outlines methodological approaches for building an effective logistic management mechanism: a transparent management system, a systemic approach (production structure analysis and decomposition), full implementation of the management cycle (planning, organizing, motivating, coordinating, controlling), a situational approach (adaptation to internal and external environmental changes), an integration approach (coordination of functions and processes), and a marketing approach (adapting logistics to market dynamics and supporting FEA competitiveness). The proposed structure of the organizational and economic mechanism of logistic management is justified as essential for enhancing the efficiency of industrial enterprises’ foreign economic activity.